Analysis of Entrepreneurship Strategies for Enhancing the Competitiveness of MSMEs Based on Local Wisdom - Yunita Tamo Ina; Katrin Adja; Michael Aleysandro Foenay; Josep F. B. Piran; Enike Tje Yustin Dima (Yayasan Pendidikan Islam Al-Matani, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy, particularly in job creation and improving community welfare. However, amid globalization and increasingly competitive markets, MSMEs are required to enhance their competitiveness. This study analyzes entrepreneurial strategies for MSMEs based on local wisdom as an effort to improve competitiveness through the integration of culture, innovation, and digital technology. The research employs a qualitative descriptive approach using literature review from recent journals, books, and academic articles. The results indicate that leveraging local wisdom such as local raw materials, cultural values, and regional specialties combined with product innovation, cultural branding, digital marketing, and storytelling can create sustainable competitive advantages. Key challenges include low digital literacy, limited access to financing, and the risk of losing authentic cultural value. Therefore, government support, inter-MSME collaboration, and training programs are crucial for the successful implementation of these strategies.